2018
DOI: 10.1159/000488928
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Fibrinogen and Factor XIII Using Double-Filtration Plasmapheresis for Antibody-Mediated Rejection: Predictive Models

Abstract: Background/Aims: Antibody-mediated rejection (AMR) is related to circulating donor-specific anti-human leukocyte antigen alloantibodies (DSAs). DSAs can be removed by apheresis, for example, double-filtration plasmapheresis (DFPP). However, DFPP removes some clotting factors (fibrinogen and factor XIII [FXIII]). Methods: This was a prospective trial including 6 DSA-mediated AMR kidney transplant recipients. Patients received 2 cycles of 3–4 consecutive DFPP sessions followed by 1 injection of rituximab (break … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…This lower volume of transfused FFP could be related to an insufficient ADAMTS13 supplementation or, on the contrary, be an indicator of a better efficacy with a lower need in FFP transfusion with DFPP. However, the safety of DFPP is discussed with risk of low blood pressure secondary to loss of albumin, hemorrhage with decrease of fibrinogen and hemolysis with filtration needing an extensive knowledge of this technique to limit these potential complications 18–21 …”
Section: Discussionmentioning
confidence: 99%
“…This lower volume of transfused FFP could be related to an insufficient ADAMTS13 supplementation or, on the contrary, be an indicator of a better efficacy with a lower need in FFP transfusion with DFPP. However, the safety of DFPP is discussed with risk of low blood pressure secondary to loss of albumin, hemorrhage with decrease of fibrinogen and hemolysis with filtration needing an extensive knowledge of this technique to limit these potential complications 18–21 …”
Section: Discussionmentioning
confidence: 99%
“…18,19 In addition, we have established a model to predict fibrinogen and FXIII depletion after DFPP sessions and this may help clinicians supplement fibrinogen and/or FXIII where appropriate. 20 Hanafusa et al studied ABOi kidney-transplant candidates and assessed the effect on factor XIII of DFPP or plasmaexchange sessions (where substitution was based on fresh frozen plasma). They reported that depletion of factor XIII was minimal with plasma exchange, whereas it was huge with DFPP.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that multiple DFPP sessions are associated with huge and long‐lasting factor XIII depletion 18,19 . In addition, we have established a model to predict fibrinogen and FXIII depletion after DFPP sessions and this may help clinicians supplement fibrinogen and/or FXIII where appropriate 20 . Hanafusa et al studied ABOi kidney‐transplant candidates and assessed the effect on factor XIII of DFPP or plasma‐exchange sessions (where substitution was based on fresh frozen plasma).…”
Section: Discussionmentioning
confidence: 99%
“…Another apheresis technique, double‐filtration plasmapheresis (DFPP), can treat larger volumes of plasma but can also significantly decrease clotting factors 7 . DFPP can be used in the setting of antibody‐mediated rejection after kidney transplantation, 7 for desensitization before ABO‐incompatible kidney transplantation, 8 but also in the setting of autoimmune disease. Recently, Cheng et al reported on a cohort of 42 patients with anti‐neutrophil cytoplasmic antibody‐associated vasculitis and renal involvement.…”
Section: Introductionmentioning
confidence: 99%